Agalsidase alfa for enzyme-replacement therapy in Fabry disease. Issue 5 (September 2010) - Mehta, Atul
Fabry disease is an X-linked lysosomal storage disorder that is caused by a deficiency in the enzyme α-galactosidase A. Manifestations emerge during childhood, including neuropathic pain, hypohidrosis and gastrointestinal problems. Major organ involvement typically occurs during adulthood and includes progressive kidney dysfunction, cardiomyopathy and valve disease, and stroke. Enzyme-replacement therapy with agalsidase alfa has been available since 2001 and is associated with clinical benefit in adult men and women, as well as in children, with Fabry disease. The responses to agalsidase alfa include reduction in the severity of neuropathic pain, stabilization of kidney function and reduction in left ventricular mass in patients with baseline left ventricular hypertrophy. Several issues, including when to initiate treatment and whether long-term treatment will extend survival, remain to be answered. This article covers the clinical development of agalsidase alfa and the postmarketing reports of its safety and effectiveness.